2022
DOI: 10.7554/elife.76132
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic atlas of Aedes aegypti reveals detailed functional organization of major body parts and gut regional specializations in sugar-fed and blood-fed adult females

Abstract: Mosquito vectors transmit numerous pathogens, but large gaps remain in our understanding of their physiology. To facilitate future explorations of mosquito biology, with specific attention to the major vector Aedes aegypti, we have created Aegypti-Atlas (http://aegyptiatlas.buchonlab.com/), an online resource hosting RNAseq profiles of Ae. aegypti body parts (head, thorax, abdomen, gut, Malpighian tubules, and ovaries), gut regions (crop, proventriculus, anterior and posterior midgut, and hindgut), and a time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 80 publications
3
52
3
Order By: Relevance
“…The midgut, MTs, and ovaries are major tissues involved in these processes following a blood meal (Hixson et al, 2022). In general, after a blood meal, we observed a complex set of changes, characterized by dynamic profiles for each receptor in the brain, midgut, MTs, and ovaries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The midgut, MTs, and ovaries are major tissues involved in these processes following a blood meal (Hixson et al, 2022). In general, after a blood meal, we observed a complex set of changes, characterized by dynamic profiles for each receptor in the brain, midgut, MTs, and ovaries.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, it is essential for the mosquito to quickly excrete toxic elements, such as heme groups (reactive species that can induce oxidative stress) and maintain salt and water homeostasis (Nikbakhtzadeh et al, 2016; Sajadi & Paluzzi, 2021). The midgut, MTs, and ovaries are major tissues involved in these processes following a blood meal (Hixson et al, 2022). In general, after a blood meal, we observed a complex set of changes, characterized by dynamic profiles for each receptor in the brain, midgut, MTs, and ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the first study characterizing immune gene transcript abundance in the Ae. aegypti crop was recently published by Hixson et al [88]. The authors propose that the predominant phenomenon in the crop would be immune recognition via orthologs of the Toll pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As bacteria transit from the mosquito crop to the midgut, gambicin and lysozyme produced in the proventriculus may exert selective pressure. In this scenario, the host's immune system would be shaping the seeding community of the posterior gut segments [88].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti atlas and Ae. aegypti developmental transcriptome by Akbari et al, in which CRVP379 is shown to be enriched in the ovaries and testes [ 37 , 38 ]. This finding was further corroborated by our western blotting and immunostaining experiments.…”
Section: Discussionmentioning
confidence: 99%